Efficient Overproduction of Active Nitrile Hydratase by Coupling Expression Induction and Enzyme Maturation via Programming a Controllable Cobalt-Responsive Gene Circuit - Han, Laichuang; Cui, Wenjing; Lin, Qiao; Chen, Qiaoqing; Suo, Feiya; Ma, Ke; Wang, Yang; Hao, Wenliang; Cheng, Zhongyi; Zhou, Zhemin (Frontiers in Bioengineering and Biotechnology, 2020)
Robust and portable expression system is of great importance in enzyme production, metabolic engineering and synthetic biology, which maximizes the performance of the engineered system. In this study, a tailor-made cobalt-induced expression system (CIES) was developed for low-cost and eco-friendly nitrile hydratase (NHase) production. First, the strong promoter Pveg from Bacillus subtilis, the Ni(II)/Co(II) responsive repressor RcnR, and its operator were re-organized to construct a cobalt-induced expression system. In this system, the expression of reporter GFP was specifically triggered by Co(II) over a broad range of concentration . The performance of the cobalt-induced system was evolved to 2.0 version (CIES 2.0) for adaptation to different concentration of Co(II) through programming a homeostasis system that rebalancing cobalt efflux and influx with RcnA and NiCoT, respectively. Harnessing these synthetic platforms, the induced expression of NHase was coupled with enzyme maturation by Co(II) in a synchronizable manner without requirement to additional inducers, which is the unique feature to other induced systems for production of NHase. The yield of NHase achieved to 111.2±17.9 U/mL by CIES and to 114.9±1.4 U/mL by CIES 2.0, which has equivalent producing capability to that of commonly used IPTG-induced systems. In scale-up system using 5-L fermenter, the yielded enzymatic activity reached 542.2±42.8 U/mL, suggesting the designer platform for NHase is readily applied to industry. The design of CIES in this study not only provided a low-cost and eco-friendly platform to over-produce NHase, but also propose a promising pipeline for development of synthetic platform for expression of metalloenzymes.